Societal dangers of migrant crisis narratives with a special focus on Belarussian and Ukrainian borders with Poland - Grabowska, Izabela (Frontiers in Sociology, 2023)
Society in the 21st century has experienced a variety of crises, from the fiscal crisis and the migration crisis to the pandemic and the inflation crisis. This paper aims to explore societal dangers of migrant crises narratives. This paper forms part of the Horizon 2020 MIMY research projects with an expert stakeholder Delphi study from seven European countries: Germany, Italy, Poland, Romania, Luxembourg, Sweden and the UK. It takes also into account contextual international and national public opinion surveys. We formulated a number of societal dangers related to the migrant crisis narrative, which are not sharp and exclusive but invite further consideration: (1) Societal fatigue, which relates to a rapid change in societal moods, usually from a positive to a negative attitude toward migrants, but above all this danger is connected with an aid burnout in a civil society; (2) Othering, which includes normativity, the labeling of migrants, double or multiple standards in the treatment of migrants and refugees from various origins; the societal danger of othering contributes to societal divisions, polarizations, tensions and conflicts based on ethnicity, religion, race and gender; (3) Political functionality, whereby migration as a political construct serves as a “whipping boy” for politicians to divert public opinion from recurrent problems; it also involves the creation of piecemeal, reactionary, ad hoc public policies, and the overuse of a protocol of a state of emergency in order to bring about a centralization of political power.